2011
DOI: 10.1007/s10815-011-9591-z
|View full text |Cite
|
Sign up to set email alerts
|

IVM is an alternative for patients with PCO after failed conventional IVF attempt

Abstract: Purpose To determine if IVM of oocytes from unstimulated cycle is a treatment option for patients who did not deliver after standard IVF-ET. Method Twenty three women with PCO, thirteen of them with normal cycles and all <35 years old, who failed IVF served as their own control. During the control IVF cycle patients were stimulated with 1730.7±639.5 IU recombinant FSH, a long Buserelin acetate protocol was used and embryo transfer was performed on day 2 or 3 after ICSI. After failed IVF immature oocytes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…The cryopreservation of GV oocytes by vitrification offers attractive perspectives [ 59 ], since the resulting GV oocytes represent an important pool of germ cells for women undergoing unstimulated IVM cycles or at risk of infertility due to ovarian hyperstimulation syndrome or polycystic ovarian syndrome, particularly in those who are poor responders to gonadotropin stimulation [ 60 ] or in the case of cancer [ 61 ]. Rescue of immature oocytes can also be performed in an IVF cycle when a conventional protocol fails to produce mature oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The cryopreservation of GV oocytes by vitrification offers attractive perspectives [ 59 ], since the resulting GV oocytes represent an important pool of germ cells for women undergoing unstimulated IVM cycles or at risk of infertility due to ovarian hyperstimulation syndrome or polycystic ovarian syndrome, particularly in those who are poor responders to gonadotropin stimulation [ 60 ] or in the case of cancer [ 61 ]. Rescue of immature oocytes can also be performed in an IVF cycle when a conventional protocol fails to produce mature oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Gulekli et al ( 46 ) studied 23 women who failed in conventional IVF and were transferred to IVM without ovarian stimulation. Only one pregnancy was obtained and that did not continue to birth, and the authors concluded that IVM might be a useful tool for failed conventional IVF ( 46 ) . As an uncommon indication, IVM may be an important optional choice in cases with oocyte maturation abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, accumulating data from articles supporting IVM because it is safe, cost-effective, simple, repeatable, flexible, and patient friendly in nature, without the risk of OHSS, it serves as a good treatment option. As such, IVF specialists need to be encouraged to add IVM to their clinical practice instead of neglecting it ( 18 , 19 , 20 , 21 ) . There are few publications regarding rescue IVM in the literature.…”
Section: Discussionmentioning
confidence: 99%